Azo-Substitute of EthoxyAcridine – A New Reagent for Extraction-Photometric Determination of Tellurium (IV) - Ismayilov, N.I.; Pashajanov, A.M.; Muradova, G.R. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
We studied associates of halogen telluride (Cl, Br) with 9-amine-4-ethoxyacridine-6-azo-N-N′-diethylaniline (AEADEA) by spectrophotometric method. It was established that associates are extracted well with chloroform-acetone (3:2). We determined the compositions, physical and chemical and analytical properties of complexes (εk, βKD, D, R%). Maximum light absorption for chloride complexes is found to be λmax 520 nm, but for bromide complexes - λmax 530 nm. For establishing the composition of azo- substitute ofethoxyacridine the synthesized reagents were exposed to elemental analysis, as well titanometrictitration by azo group. We developed new extraction-photometric determination methods of tellurium. Lambert-Beer law is observed in the range 0.5-15 mkgTe at 5 ml medium.